The principles of moral education deduced from the story of Youssef, peace be upon him, in dealing with crises and their applications in the family - Alhindi, Wjood Sameer; Alsani, Mona Mohammed (Journal of Educational and Psychological Sciences, 2022)
the aim of the research is to uncover the principles of moral education deduced from the story of Youssef, peace be upon him, in dealing with crises mentioned in the Holy Qur’an and how to apply them in the family. The researcher used both descriptive and elicit approaches. The most important results of the study: The religion of Islam is comprehensive, integrated, and valid for every time and place. It came to reform humanity and its continuity on earth by teaching them the correct methodology for dealing with all crises. Keeping away from the correct approach, deviation, and a large number of sins and disobedience, are among the causes of crises. On the other hand, repentance and seeking forgiveness are among the ways to prevent unwanted problems. Following the correct approach in dealing with life issues can guarantee that the person would be in a better situation and a less hard one. Grant, crises are not purely harmful, as they may result in many benefits. Youssef, peace be upon him, has a beautiful face and soul. His dream was fulfilled, he was reunited with his family, and he became dear to Egypt, and he overcame the crises that went through him with the kindness of his character. Among the most important recommendations of the study: It recommends the curriculum developers in the Ministry of Education to add a curriculum to deal with crises, especially with the crises that are happening now, and recommends the family to pay attention to the establishment and educate the children on the principles of dealing with crises according to their age and time. So that children can succeed and continue to strive in this world. The researcher suggests conducting studies similar to this study, related to the extraction of educational principles and applying them to our daily lives. All this is through the stories of the prophets in dealing with crises that the scholars did not discuss.